Primary Students’ School Anxiety: An Initiative Study on Virtual Reality Therapy - Anh, Doan Vi (VNU Journal of Science: Education Research; Vol 36 No 4DO - 10.25073/2588-1159/vnuer.4399, 2020)
School anxiety is an aspect of anxiety that can cause serious consequences on student’s academic results. Anxiety is usually caused by excessive stress about school related experiences. Consequently, over thinking and extreme worrying can lead to skipping classes, or even dropping out of school. Despite the emergence of school anxiety in recent years among junior students, little research on specific situations causing anxiety at school has been carried out. More importantly, very few attempts using virtual reality have been made to prepare students for a new school environment and help students with school anxiety. This study discovered 12 school experiences with high anxiety levels through questionnaires given to 229 fifth year students aged 10-11 and developed several situations into a virtual environment that can be used as a treatment program for students. 20 students with very high anxiety were chosen to experience the virtual reality (VR) treatment program. The findings show that student’s anxiety levels for the situations they have experienced in the treatment program have decreased dramatically. Students become more proactive when they handle the challenges in the program and they can even propose solutions for their problems.